2022
DOI: 10.55579/jaec.202263.378
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Fluid Flow Analysis of Shell-and-Tube Heat Exchangers with Smooth and Dimpled Tubes

Abstract: This current work mainly focuses on the enhancement of the heat transfer and fluid flow characteristics of shell-and-tube heat exchangers by incorporating dimples on the smooth or conventional tubes. With the aid of the ANSYS (Fluent) commercial software package, Computational Fluid Dynamics (CFD) simulations under a steady-state condition were conducted on heat exchanger having a single shell and 12 tubes (with or without dimples), 50% baffle cut, 100mm baffle spacing and turbulent flow. The temperature, velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Water was used as the working fluid for the mass flow rates 0.2 to 0.5 kg/s. The study reported that a triangular tube arrangement possessed the best thermal performance with a heat transfer coefficient of 2.31 kW/m 2 K. Fetuga et al [42] performed a computational study to explore the influence of dimples on the tube side of the STHE over a mass flow rate 0.2-0.5 kg/s with water as the working fluid. They concluded that there was an improvement of 14.2% in the dimpled STHE compared with the STHE with a smooth tube.…”
Section: Introductionmentioning
confidence: 99%
“…Water was used as the working fluid for the mass flow rates 0.2 to 0.5 kg/s. The study reported that a triangular tube arrangement possessed the best thermal performance with a heat transfer coefficient of 2.31 kW/m 2 K. Fetuga et al [42] performed a computational study to explore the influence of dimples on the tube side of the STHE over a mass flow rate 0.2-0.5 kg/s with water as the working fluid. They concluded that there was an improvement of 14.2% in the dimpled STHE compared with the STHE with a smooth tube.…”
Section: Introductionmentioning
confidence: 99%